Palavras à flor da pele: concepções, investimentos e verbalizações acerca do saber escrever literatura - Néo, Ana Maria Furtado (2023)
This thesis aimed to understand the meanings that high school students, in the Ceará State Education Network, attribute to their experience with literary writing in a school context, based on the conceptions, investments and verbalizations in relation to this practice of literary literacy inside and outside school. To this end, the following specific objectives guided our investigation steps: 1) analyze students' investments in relation to literary writing practices proposed and/or experienced in the school space; 2) interpret students' conceptions about writing based on their school literacy experience; 3) examine students' verbalizations about the written production process experienced at school regarding literary texts. As a theoreticalmethodological foundation, this research was based on New Studies on Literacy based on the concepts of Street (2014). The study was also conducted by the Theory of Literary Literacy (COSSON, 2006) for approaches to this more specific literacy, and, mainly, by the contributions of Barré-de-Miniac (2002; 2006) on the Theory of Relationship with Writing. This study was developed from the perspective of Qualitative Research, and the following instruments were used to collect data: the knowledge assessment and the semi-structured interview. The research subjects were students in the 1st year of high school at a state school in Ceará, in Caucaia, metropolitan region of Fortaleza. The data were analyzed using the Ideal Type method (WEBER, 1982), from which we understood three dominant trends in this relationship between students and literary writing. We conclude, therefore, that students do write literature inside and outside of school, with different objectives; whether for oneself (Catartic Writing), or for others (Expressive Writing), or for the teacher (Writing for school) and, as the school institution does not yet effectively appropriate this aesthetic action, literary writing resists a technical education and official documents, and sprouts in soil considered infertile; saving and developing writing skills previously considered inappropriate for Basic Education.